2021
DOI: 10.3390/brainsci11101301
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use among University Students and Its Relationship with Social Skills

Abstract: Internet use has been steadily and unstoppably gaining ground in all areas of life, from recreational activities to the establishment of social relations. However, addictive use of the Internet is a problem that seriously affects some people. Factors that may influence the occurrence of inappropriate internet use include age and social skills. For this reason, the aim of this study is to analyze the influence of social skills and age on the development of problematic internet use in university students. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…This study did not find the difference in IA prevalence regarding the participants’ year of study, pointing to the fact that the duration of student life itself was not a risk factor for IA, but when analyzing the prevalence of IA by students’ age groups, then this study proved that younger age of students puts them into higher risk for IA development, which is consistent with other similar studies [ 42 , 43 , 44 ] and contrary to the results of recent international study in eight countries that did not find an association between age and problematic internet use [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study did not find the difference in IA prevalence regarding the participants’ year of study, pointing to the fact that the duration of student life itself was not a risk factor for IA, but when analyzing the prevalence of IA by students’ age groups, then this study proved that younger age of students puts them into higher risk for IA development, which is consistent with other similar studies [ 42 , 43 , 44 ] and contrary to the results of recent international study in eight countries that did not find an association between age and problematic internet use [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding sociodemographic correlates, the existing literature is inconclusive on the association between age and IA. Some studies showed no association (e.g., Canan et al, 2012;Younes et al, 2016) while some studies showed a significant negative association between age and IA among university students (e.g., Kumcagiz, 2019;Miskulin et al, 2022;Orsal et al, 2013;Romero-López et al, 2021). In another study, also showed that age was negatively related to depression.…”
Section: Discussionmentioning
confidence: 95%
“…Besides IA prevalence, sociodemographic correlates of IA also deserve attention (Shek, Lee et al, in press). With regard to age, while some studies showed a negative association between age and IA (e.g., Kumcagiz, 2019;Romero-López et al, 2021), some studies revealed no association between age and IA (e.g., Cai et al, 2021). Regarding socioeconomic status, IA was found to be associated with income status under COVID-19: Olawade et al (2020) found that students who had no financial income during the pandemic were at higher risk of IA; Cai et al (2021) reported that students having poor economic status were more likely to have IA than students with fair and rich economic status.…”
Section: Internet Addiction In University Students Under Covid-19mentioning
confidence: 99%
“…However, several other reasons, beyond those strictly related to academic activities, can make university students a particularly at-risk group for the developing of IA, including the large amount of free and unstructured time available to them; possible difficulties in adapting to their new academic life and in establishing new friendships, which may expose them to more active online relationship-seeking behavior; the use of the internet as an escape route from the sources of stress related to passing exams [ 36 ]. Moreover, during young adulthood, the management of time spent on the internet is no longer under parental control and becomes an individual responsibility of the university students [ 37 , 38 ]. In the specific context of the pandemic, social distancing measures have also led to limited opportunities to socialize and establish face-to-face relationships, which in turn may increase the risk of developing IA [ 39 ].…”
Section: Introductionmentioning
confidence: 99%